God’s Freedom In Creating an Image of Human Knowledge and Human Freedom In Receiving It in Descartes’ Philosophy - Śliwiński, Tomasz (Hybris, 2012)
The topic of freedom in Descartes’ philosophy is usually being connected with human freedom. It is understood in the traditional perspective of distinguishing right from wrong and truth from false. This aspect is, in my opinion, sufficiently explained. The same applies to Descartes’ ethics, connections of which with Antiquity were often mentioned. In the paper I bring up quite different issue. It rests on the question what it means that God creates the truth and what consequences it has for human validity (and necessity) of recognizing and receiving it, what is its status and, finally, how it reconfigures the relation between God and the man.